?TOXIC EFFECTS OF ZINC ONDIFFERENT TREE SEEDLINGS - Iqbal, Muhammad Zafar; Shafiq, Muhammad (Biological Sciences - PJSIR, 1999)
Asignificantreduction inseedgermination,seedlinggrowthanddryweightofAlbizia lebbeck, Peltophorum pterocarpum. and Thespesia populnea was noted when zinc concentration was increased. A significant reduction (p<0.05) in seed germinationduetozinctoxicityat50llg ml’ wasobservedinA. lebbeck andP.pterocarpum. Higherpercentageofdecrease in seed germination of P. pterocarpum was found with 1251lg ml’ zinc treatment.The seedling length and seedling dry weight ofA. lebbeck was significantly (p<0.05) reduced with 50llg ml’ and751lg ml’ treatment of zinc respectively.